Current Economic Conditions - C., W. L.; G., R. A.; fuer Konjunkturforschung, Institut (The Review of Economics and Statistics, 1935)
W. L. C., London and Cambridge Economic Service, R. A. G., Institut fuer Konjunkturforschung, Current Economic Conditions, The Review of Economics and Statistics, Vol. 17, No. 6 (Nov., 1935), pp. 151+154-156